2022
DOI: 10.3389/fbioe.2022.890668
|View full text |Cite
|
Sign up to set email alerts
|

Superior Fluorescent Nanoemulsion Illuminates Hepatocellular Carcinoma for Surgical Navigation

Abstract: Hepatocellular carcinoma (HCC), the fifth most common cancer worldwide, poses a severe threat to public health. Intraoperative fluorescence imaging provides a golden opportunity for surgeons to visualize tumor-involved margins, thereby implementing precise HCC resection with minimal damage to normal tissues. Here, a novel-acting contrast agent, which facilely bridges indocyanine green (ICG) and lipiodol using self-emulsifying nanotechnology, was developed for optical surgical navigation. Compared to clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Based on this, our group prepared a contrast agent with excellent performance through the self-emulsification technology of lipiodol and ICG with Tween-80 for optical surgical navigation of HCC. 46 By comparison, the obtained nanoemulsion had noticeably redshifted absorption and enhanced the fluorescence signal.…”
Section: Superstable Homogeneous Intermixed Formulation Technology (S...mentioning
confidence: 95%
See 2 more Smart Citations
“…Based on this, our group prepared a contrast agent with excellent performance through the self-emulsification technology of lipiodol and ICG with Tween-80 for optical surgical navigation of HCC. 46 By comparison, the obtained nanoemulsion had noticeably redshifted absorption and enhanced the fluorescence signal.…”
Section: Superstable Homogeneous Intermixed Formulation Technology (S...mentioning
confidence: 95%
“…This emulsion was effective at overcoming the diffusion and depth limitations of an ICG solution administered alone and had great potential to facilitate accurate localization and resection of pulmonary nodules during minimally invasive procedures. Based on this, our group prepared a contrast agent with excellent performance through the self-emulsification technology of lipiodol and ICG with Tween-80 for optical surgical navigation of HCC . By comparison, the obtained nanoemulsion had noticeably red-shifted absorption and enhanced the fluorescence signal.…”
Section: Superstable Homogeneous Intermixed Formulation Technology (S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, since optical imaging could perform high space-time resolution, fluorescent probe-based bioimaging has become the most popular real-time biological process imaging technique, which provides varied information for biological research ( Li et al, 2013 ; Jeong et al, 2018 ; Zhao et al, 2018 ; Yang et al, 2020 ; Fang et al, 2021 ; Ghanim et al, 2021 ). Recently, there are some reports about smart nanomaterials which are applied in biosensing and therapy ( Yi et al, 2022 ; Zheng et al, 2022 ; Zhu et al, 2022 ). Conventional fluorescent probes in the visible region always suffer from tissue scattering, autofluorescence, etc., resulting in low tissue penetration depth and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, He et al reported a superstable homogeneous lipiodol-hydrophilic chemodrug formulation for TACE of HCC ( He et al, 2022 ), which significantly enhanced the dispersion of chemotherapeutic drugs in lipiodol, thereby increasing the drug bioavailability of TACE in HCC patients and overcoming the shortcoming of rapid drug-releasee in clinic. Compared with the conventional surfactant emulsion strategy to increase drug dispersibility ( Zhu et al, 2022 ), this superstable homogeneous intermixed formulation technology (SHIFT) is a green manufacture with any additions ( Chen et al, 2020a ; Cheng et al, 2020 ). And the chemotherapeutic drugs are assembled into nanostructures under the condition of cardon dioxide supercritical fluid.…”
Section: Introductionmentioning
confidence: 99%